Online Learning For Primary School Students In Indonesia During Covid-19 Pandemic - et. al., Hariyadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the barriers, solutions, and projections of online learning during the Covid-19 pandemic in Indonesian Primary Education students. The nature of this research is qualitative research by using the sourced from the Ministry of Education website namely 'Sahabat Keluarga Kemendikbud'. The data taken was from the survey which was conducted by the UNICEF on 18-29 May 2020 and 5-8 June 2020. During the survey, UNICEF received more than 4,000 responses from students in 34 Indonesian provinces, through the U-Report channel which consists of the Short Message System (SMS), WhatsApp, and Facebook Messenger. One of the teacher's obstacles when doing online learning is the students' lack of understanding of the lesson because the teachers are not able to explain the lesson face to face with the students.